Pemanfaatan Gold Nano Particles Untuk Deteksi Dan Terapi Kanker Pada Manusia - Ali, Lalu Usman; Suryana, Risa; Taher, Tamrin (Alpatih Harapan Semesta, 2024)
Research on the utilization of Gold Nanoparticles (GNPs) has rapidly advanced in recent decades, particularly in the biomedical field for cancer detection and therapy. GNPs have unique characteristics, such as nanometer size, high chemical stability, modifiable optical properties, and good biocompatibility, making them ideal candidates for applications in nanomedicine. This literature reviews the utilization of GNPs in cancer detection through local surface plasmon resonance (LSPR)-based imaging techniques, signal enhancement in Raman spectroscopy, and the delivery of specific diagnostic agents. Additionally, in cancer therapy, GNPs are used for photothermal, photodynamic, and targeted drug delivery, which can enhance therapeutic efficacy and reduce side effects on healthy tissues. This literature review also covers the main challenges in the development of GNP-based technologies, including toxicity, in vivo stability, and production scalability. The results of this study indicate that GNPs have great potential for clinical application, although further research is needed to address technical and ethical constraints before they can be widely implemented in cancer treatment in humans